Burden of Atrial Fibrillation and Atrial Flutter From 1990 to 2021 in China: Global Burden of Disease Study 2021 Update. - Kong, Xiangyi; Li, Mingxiao; He, Liu; Lai, Yiwei; Wang, Jue; Li, Sitong; Peng, Xiaodong; Zhao, Manlin; Li, Qifan; Zhao, Zixu; Zhou, Le; Yang, Zejun; et al. (Pacing & Clinical Electrophysiology, 2025)
Background: Atrial fibrillation (AF) and atrial flutter (AFL) represent increasingly significant health burden globally. We aimed to systematically evaluate the status and trends of AF/AFL burden and attributable risk factors in China. Methods: We assessed the burden of AF/AFL measured as prevalence, incidence, mortality, and disability‐adjusted life years (DALYs), by sex and age groups in China based on the Global Burden of Diseases Study (GBD) 2021 project. Results: In China, there were 10,775.72 thousand AF/AFL prevalent cases, 916.18 thousand AF/AFL incident cases, and 64.73 thousand AF/AFL mortality cases, contributing to 1653.12 thousand DALYs due to AF/AFL in 2021. Trend analysis indicated that the AAPC of number and crude rates of prevalence, incidence, mortality, and DALYs all escalated from 1990 to 2021. The current AF/AFL burden and temporal trend between 1990 and 2021 displayed heterogeneity based on sex and age groups. The spectrum for risk factors attributed for DALYs due to AF/AFL presented sex‐ and age‐specific manifestation. High systolic blood pressure served as the emerging leading contributor to DALYs due to AF/AFL in China. Conclusion: A significant increase in the burden of AF/AFL underscores the enduring public health burden of AF/AFL in China, marked by profound sex and age‐related variations. There is a pressing imperative to adopt tailored strategies to attenuate increasing burden of AF/AFL and combat alongside high complication burden due to AF/AFL in China.